Abstraction and Artifice in Twentieth-Century Art - Osborne, Harold; Clarendon Press, Oxford (Oxford : Oxford university press, 1979)
Contents: Part One: Modus of Abstraction ; Part Two: Abstraction from Nature ; Part Three: Constructivist Abstraction
Engels
boek